Hydrogen Isotope Exchange with Superbulky Alkaline Earth Metal Amide Catalysts - Martin, Johannes; Eyselein, Jonathan; Grams, Samuel; Harder, Sjoerd (ACS Catalysis, 2020)
Heavier alkaline earth (Ae) metal amide complexes hydrogen isotope exchange (HIE). The activities for D/H exchange Ae(NR2)(2) (Ae = Ca, Sr, Ba) were found to be highly active catalysts for between C6D6 and H-2 strongly increase with metal size (Ca < Sr < Ba) and with amide bulk: N(SiMe3)(2) < N(DIPP)(SiiPr(3))< N(SiiPr(3))(2), DIPP = 2,6-diisopropylphenyl. At 120 degrees C and pressures of 10-50 bar, no hydrogenation side-products are produced, and TONs of 205 and TOFs of 268, competitive with those for precious metal catalysts, have been achieved. The reverse H/D exchange between C6H6 and D-2 is even faster by a factor 1.5-2. Substrates also include a range of substituted arenes. Alkyl-substituted aromatic rings are preferably deuterated in acidic benzylic positions, and this tendency increases with the number of alkyl-substituents. Although unactivated (sp(3))C-H units could not be deuterated, the (sp(3))Si-H function in primary, secondary, and tertiary alkylsilanes could be converted. Two different pathways for C6H6/D-2 isotope exchange have been evaluated by DFT calculations: (A) a deprotonation/protonation mechanism and (B) direct nucleophilic aromatic substitution. Although the exact nature of the catalyst(s) is unclear, the first step is the conversion of Ae(NR2)(2) with D-2 into R(2)NAeD which can aggregate to larger clusters. Energy profiles with model catalysts (iPr(3)Si)(2)NAeD and [(Me3Si)(2)NAeD](2) (Ae = Ca or Ba) show that the direct nucleophilic aromatic substitution is the most likely mechanism for deuteration of arenes. The key to this unusual reaction is the initial formation of a pi-arene center dot center dot center dot Ae complex which is followed by the generation of an intermediate with a Meisenheimer anion. Heavier Ae metal amide complexes are, despite the lack of partially filled d-orbitals for substrate activation, potent catalysts for HIE.
CRIS-Team WoS Importer:2020-08-14